Implementasi Keterampilan Menulis Teks Sastra Cerpen Melalui Media Audio Visual Pada Siswa Kelas V UPT SDN No. 78 Balang Desa Bontokassi Kecamatan Galesong Selatan Kabupaten Takalar - Nurannisa; Nur Ummi Kalsum; Nasrun; Syamsinah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to improve short story writing skills through the use of audio-visual media for fifth-grade students at UPT SDN No.78 Balang, Galesong Selatan District, Takalar Regency. The background of this research is the low ability of students in writing short stories, particularly in structuring the plot, describing characters, and presenting conflicts and moral messages. The method used is Classroom Action Research (CAR) with the Kemmis and McTaggart model, conducted in four cycles, each consisting of eight meetings. The research subjects were 37 fifth-grade students. Data were collected through observation, short story writing tests, and documentation, then analyzed both qualitatively and quantitatively. The results showed a significant improvement in students’ short story writing skills, with the percentage of mastery learning increasing from 45.9% in cycle I to 91.9% in cycle IV. Improvements were observed in students’ ability to organize plots, develop characters, describe settings, present conflicts, and convey moral messages. In addition, the use of audio-visual media was proven to enhance students’ motivation, creativity, and participation in learning. Thus, audio-visual media can serve as an innovative, effective, and engaging learning strategy to improve elementary school students’ short story writing skills.